Barrier-Free Carrier Injection in 2D WSe2-MoSe2 Heterostructures via Fermi-Level Depinning - Tian-Jun Dai; Xiang Xiao; Zhong-Yuan Fan; Zi-Yan Zhang; Yi Zhou; Yong-Chi Xu; Jian Sun; Xue-Fei Liu (Nanomaterials)
Fermi-level pinning (FLP) at metal–semiconductor interfaces remains a key obstacle to achieving low-resistance contacts in two-dimensional (2D) transition metal dichalcogenide (TMDC)-based heterostructures. Here, we present a first-principles study of Schottky barrier formation in WSe2-MoSe2 van der Waals heterostructures interfaced with four representative metals (Ag, Al, Au, and Pt). It was found that all metal–WSe2/MoSe2 direct contacts induce pronounced metal-induced gap states (MIGSs), leading to significant FLP inside the WSe2/MoSe2 band gaps and elevated Schottky barrier heights (SBHs) greater than 0.31 eV. By introducing a 2D metal-doped metallic (mWSe/mMoSe) layer between WSe2/MoSe2 and the metal electrodes, the MIGSs can be effectively suppressed, resulting in nearly negligible SBHs for both electrons and holes, with even an SBH of 0 eV observed in the Ag-AgMoSe-MoSe2 contact, thereby enabling quasi-Ohmic contact behavior. Our results offer a universal and practical strategy to mitigate FLP and achieve high-performance TMDC-based electronic devices with ultralow contact resistance.